Evaluation of Solid Medical Waste Management at Prof. Dr. W. Z. Johannes Kupang Hospital (International Journal of Scientific Research and Management (IJSRM), 2016)
Background : Analyze resources in the management of solid medical waste include : Human Resources (quality and quantity), costs, facilities, Standard Operating Procedures (SOP), operational technique, output of solid medical waste management at hospital. Analyze phases of solid medical waste management process includes : a source of waste, minimization, segregation, collection, transportation, temporary storage, processing and final disposal. Methods : This is a evaluation research which describe medical solid waste management system. Result :Analyze the results of medical solid waste management include : the conditions in temporary storage and the final disposal. Minimization stages acquire good category with score 86,11%, segregation stages acquire sufficient category with score 67,33%, collecting stages acquire good category with score 88,89%, transportation stages acquire good category with score 84,72%, temporary storage stages acquire sufficient category with score 75,40%, processing stages acquire sufficient category with score 58,33% and final disposal stages acquire sufficient category with score 70,63%. Conclusion : For human resources in the management of solid medical waste in hospitals Prof. Dr. Z. W. Johannes Kupang, sanitary installations officers have not been trained in the management of solid medical waste hospitals, infrastructure is still lacking, socialization SOP related waste management is still lacking. TPS condition in a permanent housing is open, so no unauthorized parties can enter and not free from vermin. No incidence of occupational accidents resulting solid medical waste includes physical injury